Mode-switching induced super-thermal bunching in quantum-dot microlasers. (9th June 2016) - Redlich, Christoph; Lingnau, Benjamin; Holzinger, Steffen; Schlottmann, Elisabeth; Kreinberg, Sören; Schneider, Christian; Kamp, Martin; Höfling, Sven; Wolters, Janik; Reitzenstein, Stephan; Lüdge, Kathy
Abstract: The super-thermal photon bunching in quantum-dot (QD) micropillar lasers is investigated both experimentally and theoretically via simulations driven by dynamic considerations. Using stochastic multi-mode rate equations we obtain very good agreement between experiment and theory in terms of intensity profiles and intensity-correlation properties of the examined QD micro-laser's emission. Further investigations of the time-dependent emission show that super-thermal photon bunching occurs due to irregular mode-switching events in the bimodal lasers. Our bifurcation analysis reveals that these switchings find their origin in an underlying bistability, such that spontaneous emission noise is able to effectively perturb the two competing modes in a small parameter region. We thus ascribe the observed high photon correlation to dynamical multistabilities rather than quantum mechanical correlations.